2021
DOI: 10.1182/blood.2020005865
|View full text |Cite
|
Sign up to set email alerts
|

The characterization of distinct populations of murine skeletal cells that have different roles in B lymphopoiesis

Abstract: Hematopoiesis is extrinsically controlled by cells of the bone marrow microenvironment, including skeletal lineage cells. The identification and subsequent studies of distinct subpopulations of maturing skeletal cells is currently limited due to a lack of methods to isolate these cells. We found that murine Lineage-CD31-Sca-1-CD51+ cells can be divided into four subpopulations using flow cytometry, based on their expression of the platelet derived growth factor receptors ⍺ and β (PDGFR⍺ and PDGFRβ). The use of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 71 publications
0
23
0
Order By: Relevance
“…BM stromal cells include a variety of non-hematopoietic cells, such MSCs and OBs, which are the precursors of mature mineralized OCYs, and ECs. All of these cells support B cell development (1, 28,31,32). In our study, using flow cytometry after bone digest, we found that the distribution of the stromal cell populations was not affected in the VhlcKO, with the exception of CD31+ ECs, which were reduced.…”
Section: Discussionmentioning
confidence: 51%
“…BM stromal cells include a variety of non-hematopoietic cells, such MSCs and OBs, which are the precursors of mature mineralized OCYs, and ECs. All of these cells support B cell development (1, 28,31,32). In our study, using flow cytometry after bone digest, we found that the distribution of the stromal cell populations was not affected in the VhlcKO, with the exception of CD31+ ECs, which were reduced.…”
Section: Discussionmentioning
confidence: 51%
“…A recent study described that there are at least five different types of skeletal‐derived cell types that line endosteal surfaces, four of these co‐express CD51 + , lack Sca‐1 expression, and can be further subdivided by their expression of platelet‐derived growth factor receptor α (PDGFRα) and PDGFRβ. ( 22 ) These four novel skeletal cell types have been shown to have distinct functional potential, including support of B lymphopoiesis, and some of these cell types express high levels of HSC regulatory molecules. Multiplex immunofluorescence studies revealed that the four populations of CD51 + Sca‐1 − cells localized to the growth plate and/or trabecular, but not cortical, endosteal bone surfaces in tibias of mice.…”
Section: Microenvironmental Alterations Cause a Loss Of Normal Hematopoiesismentioning
confidence: 99%
“…The described cellular and molecular components of the HSC niche ( 3 ) are continuously expanding, and today include both endosteal and endothelial components such as: mesenchymal stromal cells (MSCs), ( 4–6 ) arteriolar ( 7 ) and sinusoidal ( 8,9 ) endothelial cells (ECs), osteoblasts (OBs), ( 10–13 ) spindle‐shaped N‐cadherin + CD45 − osteoblastic cells (SNO cells), ( 12 ) macrophages, ( 14 ) megakaryocytes, ( 15 ) T cells, ( 16 ) the sympathetic nervous system (SNS) through β‐adrenergic signaling, ( 17,18 ) perivascular stromal cells ( 19 ) including LepR + skeletal stem cells, ( 20 ) chemokine (C‐X‐C motif) ligand 12 (CXCL12)‐abundant reticular (CAR) cells, ( 21 ) skeletal lineage cells, ( 22 ) Schwann cells, ( 23 ) and adipocytes. ( 24,25 ) These niche cells produce numerous regulatory factors that are vital for HSC quiescence and regeneration, and control of differentiation, including various cell‐surface proteins, extracellular cytokines, and inflammatory molecules, such as CXCL12, ( 5,21 ) angiopoietin‐1 (Ang‐1), ( 26 ) thrombopoietin (TPO), ( 27 ) stem cell factor (SCF), ( 28 ) C‐C motif chemokine ligand 3 (CCL3), ( 29,30 ) and angiogenin (ANG), ( 31 ) as well as variable oxygen tension and reactive oxygen species (ROS).…”
Section: Introductionmentioning
confidence: 99%
“…We have recently used such an approach to FACS isolate and characterize four novel BM stromal cells from mouse collagenase‐digested long bones 152 . The cells were defined by their lack of expression of hematopoietic and endothelial cell lineage markers and were CD51 positive but lacked expression of Sca‐1.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…It would be of interest to study human biopsy samples to further elucidate human B lymphopoiesis and the interactions of distinct developing B lymphocyte populations with different BM stromal cell types. Advancements in imaging technologies such as Opal TM multiplexing studies are making such studies more accessible 152,157 . Furthermore, single cell RNA‐seq studies of human bone marrow cells will provide insight into the stromal cell types that support human B lymphopoiesis.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%